(untitled) - Wartick, Steven L. (Malden, Massachusetts, 1998)
The book explores the breadth of business and society topics - corporate social performance, business ethics, business-government relations, stakeholder management, and issues management/public affairs - within the broader context of the international environment
Keywords: Business and politics,Business ethics,International business enterprises,Social responsability of business; Social aspects